2009
DOI: 10.1007/s11671-009-9316-8
|View full text |Cite
|
Sign up to set email alerts
|

On the Enhanced Antibacterial Activity of Antibiotics Mixed with Gold Nanoparticles

Abstract: The bacterial action of gentamicin and that of a mixture of gentamicin and 15-nm colloidal-gold particles onEscherichia coliK12 was examined by the agar-well-diffusion method, enumeration of colony-forming units, and turbidimetry. Addition of gentamicin to colloidal gold changed the gold color and extinction spectrum. Within the experimental errors, there were no significant differences in antibacterial activity between pure gentamicin and its mixture with gold nanoparticles (NPs). Atomic absorption spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(97 citation statements)
references
References 51 publications
5
92
0
Order By: Relevance
“…In this study, no significant difference was observed between antibacterial activity of antibiotics alone and their mixture with Au NPs. However, as suggested by Burygin et al, it seems that Au NPs enhance antibacterial activity of antibiotics only when antibiotic is chemically attached on the surface of Au NPs and formed stable conjugates with particles rather than when used in combination with antibiotics as a mixture [29]. Therefore, comparing Au NPs and Au…”
Section: Resultsmentioning
confidence: 97%
“…In this study, no significant difference was observed between antibacterial activity of antibiotics alone and their mixture with Au NPs. However, as suggested by Burygin et al, it seems that Au NPs enhance antibacterial activity of antibiotics only when antibiotic is chemically attached on the surface of Au NPs and formed stable conjugates with particles rather than when used in combination with antibiotics as a mixture [29]. Therefore, comparing Au NPs and Au…”
Section: Resultsmentioning
confidence: 97%
“…28 These charged stabilized nanoparticles have been attached or bioconjugated with a variety of photosensitizers and antibiotics. 61,30 Earlier studies have been performed against pathogenic microbes by amalgamating the properties of both colloidal GNP and thiazine dyes such as MB and TBO as a GNP-thiazine conjugate. In one of the studies, GNP conjugated with TBO showed effective PDT against Staphylococcus aureus and enhanced the bactericidal effect up to 90%-99%.…”
Section: Discussionmentioning
confidence: 99%
“…Using different methods of preparation, Au-based nanomaterials such as Au nanospheres, Au nanostars, and Au nanorods can be obtained to inactive bacteria by a photothermic process [73]. Thus, Au-nanoparticles can be conjugated with specific antibody [74], PSs [75], and antibiotics [76], or have intrinsic antibacterial activity [77,78].…”
Section: Photomedicine -Advances In Clinical Practicementioning
confidence: 99%